Microscopic evidence for Mn-induced long range magnetic ordering in MAX phase compounds. (15th October 2020) - Maniv, A; Reyes, A P; Ramakrishna, S K; Graf, D; Huq, A; Potashnikov, D; Rivin, O; Pesach, A; Tao, Q; Rosen, J; Felner, I; Caspi, E N
Abstract: Zero and low field nuclear magnetic resonance measurements have been performed on MAX phase samples (Cr1− x Mn x )2 AC with A = Ge and Ga in order to obtain local microscopic information on the nature of magnetism in this system. Our results unambiguously provide evidence for the existence of long-range magnetic order in (Cr0.96 Mn0.04 )2 GeC and for (Cr0.93 Mn0.07 )2 GaC, but not for (Cr0.97 Mn0.03 )2 GaC. We point to a possible dependence of long range magnetic order in these MAX phase compounds on the A atom.